1999
DOI: 10.1097/00004647-199909000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Early Training May Exacerbate Brain Damage after Focal Brain Ischemia in the Rat

Abstract: Summary: Early overuse of a lesioned forelimb, induced by immediate immobilization of the intact forelimb after a cortical lesion, has been reported to increase tissue damage and delay functional recovery. To investigate if early training without immobilization of the intact forelimb could increase tissue loss and reduce recovery, the middle cerebral artery was ligated distal to the striatal branches in 25 male spontaneously hyper tensive rats. Control rats were housed in standard cages, train ing rats were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
6
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(126 citation statements)
references
References 55 publications
7
109
6
4
Order By: Relevance
“…15,[62][63][64][65][66] Considerable progress is being made in designing useful, evidence-based outcome measures for human stroke diagnosis and research. It is not easy to match deficits in rats and people, but test selection and interpretation of the nature of the deficit is critical in both if translational research is to be successful.…”
Section: Resultsmentioning
confidence: 99%
“…15,[62][63][64][65][66] Considerable progress is being made in designing useful, evidence-based outcome measures for human stroke diagnosis and research. It is not easy to match deficits in rats and people, but test selection and interpretation of the nature of the deficit is critical in both if translational research is to be successful.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies noted an exacerbation of injury and worsened overall outcome after excessive use of the impaired limbs (i.e., by casting or enrichment) beginning immediately after the injury (Kozlowski et al, 1996;Risedal et al, 1999). Other studies report that despite exacerbation of ischemic injury, immediate exposure to environmental enrichment improves functional outcome (Risedal et al, 1999;Farrell et al, 2001), perhaps as a result of removing functionally abnormal neurons.…”
Section: Early Rehabilitation (Er5) Does Not Exacerbate Infarct Size mentioning
confidence: 99%
“…In 1999, Risedal et al 4 reported the negative effect of early training after focal brain ischemia in their animal study, by demonstrating more prominent increased infarct volume and thalamic atrophy in the early training group than the standard and late rehabilitation group. The functional recovery was also seen delayed in the early training group, whereas the late rehabilitation group swam shorter distance, and found platform earlier than the early training group in the water maze test.…”
Section: ) Animal Studiesmentioning
confidence: 99%
“…1 Adaptive plasticity in the lesioned side of the brain as well as the healthy side by rehabilitational training was observed in many clinical and experimental studies. 4 Horn et al 2 found earlier rehabilitation admission and higher level activities early in the rehabilitation process are associated with better stroke outcome.…”
Section: Introductionmentioning
confidence: 99%